Grid-Rod Grounding With Gypsum Additive Media In Narrow Rocky Soil Areas - Suartika, Made; Janardana, I Gusti Ngurah (Journal of Electrical, Electronics and Informatics; Vol 8 No 1 (2024): JEEI (June 2024), 2024)
Rocky soil with soil resistivity (?) > 200 ?-meter is very difficult to install a grounding system by obtaining a very small grounding resistance value, so it requires a grounding system with a large area.The location of the PLN distribution substation has a maximum area of ??20 m 2 , so a Grid or Grid-rod grounding system with narrow land is needed, so that a decrease in the soil resistivity value is needed.  The purpose of this study was to apply gypsum additives to reduce the value of soil resistivity. The results showed that the addition of gypsum additives to limestone soils was very effective in reducing the soil resistivity value from 251.20 ohm-meters to 163.28 ohm-meters or a decrease of 35%. The 35% reduction in the soil resistivity value had an impact on the grounding structure in narrow areas of calcareous soil including: a depth of 2.5 meters, a form of grounding in the form of a grid rod, a reduction in the total length of the mesh conductor from 200 meters to 140 meters (a reduction in the length of the conductor by 30%), reducing the length of the electrode rod from 5000 meters to 2450 meters (reducing the length of the electrode rod by 51%), the size of the grounding system, even in a narrow area of ??2 meters x 2 meters, can still be developed for the grounding system.Keywords : Gypsum, Grid-rod, Narrow land earthing,